2017
DOI: 10.1002/jssc.201701205
|View full text |Cite
|
Sign up to set email alerts
|

One‐pot synthesis of a multi‐template molecularly imprinted polymer for the extraction of six sulfonamide residues from milk before high‐performance liquid chromatography with diode array detection

Abstract: A highly selective molecularly imprinted polymer sorbent was synthesized and employed for the simultaneous determination of six sulfonamide antibiotic residues (sulfanilamide, sulfacetamide, sulfadiazine, sulfathiazole, sulfamerazine, and sulfamethizole) in milk samples. Multi-analyte imprinted particles were used as a sorbent in solid-phase extraction. Sulfonamides were separated on a high-performance liquid chromatography column (Merck-Lichrospher RP18e, 5 μm 250 × 4 mm) and further identified and quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…Interesting approaches include FPSE [60], GMeS microextraction [61], and mini-SAE [62]. Reported novel materials include a magnetic hyper cross-linked polystyrene composite [58] and a magnetic graphene-based composite [59] utilized in MSPE protocols and multi-template MIPs prepared by sol-gel synthesis utilized in a SPE protocol [56]. Furthermore, SLE [63], QuEChERS extraction [64], and IL-MB-LPME [65] were reported for the extraction of SAs from milk products.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interesting approaches include FPSE [60], GMeS microextraction [61], and mini-SAE [62]. Reported novel materials include a magnetic hyper cross-linked polystyrene composite [58] and a magnetic graphene-based composite [59] utilized in MSPE protocols and multi-template MIPs prepared by sol-gel synthesis utilized in a SPE protocol [56]. Furthermore, SLE [63], QuEChERS extraction [64], and IL-MB-LPME [65] were reported for the extraction of SAs from milk products.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis was carried out by HPLC-DAD. MISPE cartridge conditioning was omitted as an unnecessary step, thus reducing the time of the developed sample preparation protocol [56].…”
Section: Spementioning
confidence: 99%
See 1 more Smart Citation
“…Polymers [117][118][119][120][121], molecularly imprinted polymers (MIPs) [47,[122][123][124][125][126], MOFs [127][128][129][130], and COFs [35,[131][132][133][134] have been utilized in the sensitive detection of sulfonamides. Their fascinating characteristics improve the enrichment performance.…”
Section: Adsorbentmentioning
confidence: 99%
“…Sulfonamides (SAs) are widely employed as anti‐infection drugs against human and animal disease, due to their low cost and broad‐spectrum antimicrobial activity . However, it has been reported that most SAs cannot be completely absorbed by organisms; hence, they are discharged into the ambient environment in their original form or as metabolites .…”
Section: Introductionmentioning
confidence: 99%